2011
DOI: 10.1021/pr100706k
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Mouse Oocytes Reveals 28 Candidate Factors of the “Reprogrammome”

Abstract: The oocyte is the only cell of the body that can reprogram transplanted somatic nuclei and sets the gold standard for all reprogramming methods. Therefore, an in-depth characterization of its proteome holds promise to advance our understanding of reprogramming and germ cell biology. To date, limitations on oocyte numbers and proteomic technology have impeded this task, and the search for reprogramming factors has been conducted in embryonic stem (ES) cells instead. Here, we present the proteome of metaphase II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
102
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 110 publications
3
102
0
Order By: Relevance
“…In mouse oocytes, mRNAs for all six Set1/Trithorax-type members, Setd1a, Setd1b and Mll1-4, are expressed (Kageyama et al, 2007;Andreu-Vieyra et al, 2010;Pfeiffer et al, 2011;Bledau et al, 2014;Aoshima et al, 2015). To date, we have conditionally mutated Mll1, Mll2, Setd1a and Setd1b using Gdf9-iCre to establish that only oocyte-specific deletion of Setd1b and Mll2 perturb fertility (Andreu-Vieyra et al, 2010;Bledau et al, 2014; this paper; and A.K., Q.Z., K.A.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse oocytes, mRNAs for all six Set1/Trithorax-type members, Setd1a, Setd1b and Mll1-4, are expressed (Kageyama et al, 2007;Andreu-Vieyra et al, 2010;Pfeiffer et al, 2011;Bledau et al, 2014;Aoshima et al, 2015). To date, we have conditionally mutated Mll1, Mll2, Setd1a and Setd1b using Gdf9-iCre to establish that only oocyte-specific deletion of Setd1b and Mll2 perturb fertility (Andreu-Vieyra et al, 2010;Bledau et al, 2014; this paper; and A.K., Q.Z., K.A.…”
Section: Discussionmentioning
confidence: 99%
“…PAPOLA is also one of the 118 proteins with no detected cognate mRNA, together with HDAC1/2 (member of the 'reprogrammome'; Supplementary Fig. 3, see section on supplementary data given at the end of this article; Pfeiffer et al 2011), suggesting that the amount of enzyme for these two factors may not be replenished without de novo transcription. We speculate that this might be a fatal hurdle for SCNT embryos because de novo transcription of the Papola gene is dependent on prior nuclear reprogramming, which is known to be inefficient.…”
Section: Discussionmentioning
confidence: 99%
“…During the past decades, several approaches analyzing the protein composition of oocytes have been conducted to obtain the proteome signatures of Xenopus, bovine, pig, and mouse oocytes (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Calvert et al (15) identified eight highly abundant heat shock proteins and related chaperones in the mature mouse egg by two-dimensional difference gel electrophoresis (DIGE).…”
mentioning
confidence: 99%